2011
DOI: 10.1016/j.molcel.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD-Box Protein Ded1 Modulates Translation by the Formation and Resolution of an eIF4F-mRNA Complex

Abstract: Summary The translation, localization, and degradation of cytoplasmic mRNAs are controlled by the formation and rearrangement of their mRNPs. The conserved Ded1/DDX3 DEAD-box protein functions in an unknown manner to affect both translation initiation and repression. We demonstrate that Ded1 first functions by directly interacting with eIF4G to assemble a Ded1-mRNA-eIF4F complex, which accumulates in stress granules. Following ATP hydrolysis by Ded1, the mRNP exits stress granules and completes translation ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
332
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(364 citation statements)
references
References 37 publications
(67 reference statements)
30
332
0
2
Order By: Relevance
“…Ded1 binds the RNA3 motif at the C terminus of eIF4G1 (Hilliker et al 2011). While mutational inactivation of Ded1 inhibits translation initiation (Chuang et al 1997), its overexpression rescues eIF4E ts alleles (de la Cruz et al 1997).…”
Section: Mrna Recruitment Of the 43s Picmentioning
confidence: 99%
“…Ded1 binds the RNA3 motif at the C terminus of eIF4G1 (Hilliker et al 2011). While mutational inactivation of Ded1 inhibits translation initiation (Chuang et al 1997), its overexpression rescues eIF4E ts alleles (de la Cruz et al 1997).…”
Section: Mrna Recruitment Of the 43s Picmentioning
confidence: 99%
“…One of these is additional eIF4A for which one might imagine a mechanism (60). The others represent different RNA helicases including DDX3, DDX41, DHX9, and DHX29 (61)(62)(63)(64). These alternate possibilities are extensively reviewed in Parsyan et al (65).…”
Section: Other Complicationsmentioning
confidence: 99%
“…55,[58][59][60] In this process, these enzymes are delivered to the 5 0 end of the mRNA either by binding to a specific post-transcriptional element (PCE) in the case of RHA, as part of the eIF4F complex for Ded1, or together with the 40S ribosomal subunit for DHX29. [60][61][62] In the case of HIV-1, BorisLawrie and colleagues have addressed the role of DHX9/RHA in viral translation and they showed that the latter was required to promote RNP remodeling through the 5 0 UTR to ensure ribosome progression. 61 This occurs by the initial binding of RHA to the PCE element found in the HIV-1 5…”
Section: The Need For Additional Helicases In Hiv-1 Translationmentioning
confidence: 99%